Selective targeting of homologous recombination deficiency - Zimmer, J (2014)
Homologous recombination (HR) is a key DNA repair pathway essential for cell viability. Counter-intuitively, HR deficiency can trigger carcinogenesis. Understanding the mechanisms that allow the rampant proliferation of HR-deficient tumour cells is crucial for the development of improved therapeutic modalities to selectively inhibit the outgrowth of these cells. Recently, we identified extracellular signal-regulated kinase 1 (ERK1) as a factor required for the proliferation of BRCA2-deficient cells regardless of their p53 status (Carlos et al., 2013). Here, we report the therapeutic potential of two chemical ERK1/2 inhibitors, SCH772984 and VTX-11e, for selective targeting of HR-deficient tumours due to their ability to specifically obstruct proliferation of HR-deficient cells. G-quadruplexes (G4s), secondary DNA structures formed by guanine-rich (G-rich) single-stranded DNA (ssDNA), represent natural barriers to replication fork progression. In this study, we demonstrate that treatment with G4 stabilisers selectively decreases viability of BRCA2- and RAD51-deficient cells. We identify DNA damage response activation and acute replication stress as main sources for the cellular toxicity of G4 stabilisers specifically in the context of HR deficiency. Taken together, the results presented here indicate that HR is required for replication of genomic regions with G4-forming potential to prevent genomic instability stemming from inefficient replication of these sites. Persistent G4 structures lead to DNA damage accumulation, which enables selective killing of cells whose HR-mediated repair has been compromised. This is an important finding with profound implications for the therapeutic exploitation of HR deficiency in the clinic.